Filiation in the Moroccan Mudawwana twenty years later. The persistence of discrimination - Garratón Mateu, Carmen (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
Moroccan Family Code is currently in the process of being deeply reformed that is expected to end throughout 2024. Almost twenty years after its promulgation and despite the social and legal changes experienced in Morocco there are however problems of incompatibility among this regulation, the Moroccan Constitution and the international conventions ratified by Morocco. Based on this approach, this work undertakes a descriptive-legal analysis of the above-mentioned law with the aim of highlighting the legal contradictions and the continued existence of discriminatory legal precepts in matters of filiation, the legal gaps that deliberately do not provide a response to the new models of family of society today and the expectations yet to be fulfilled.
Keywords: gender inequality; single motherhood; illegitimate filiation; discrimination based on filiation; male domination